The impact of physical exercise with additional visual tasks on UDVA and accommodation sensitivity in children: the mediating role of kinetic visual acuity - Wang, Miyu; Zhu, Guiming; Li, Yihua; Li, Pengfei; Shi, Haijie; Jiang, Limei; Diao, Yucui; Yin, Rongbin (Frontiers in Public Health, 2024)
PurposeThis study investigates the impact of physical exercise supplemented with visual tasks on children’s uncorrected distance visual acuity (UDVA), kinetic visual acuity (KVA), and accommodative sensitivity, with an analysis of the mediating role of KVA.MethodsA total of 168 third-grade students from four natural classes in a primary school in Suzhou City were randomly assigned to either an experimental group (n = 86) or a control group (n = 82). The experimental group engaged in 30 cycles of ciliary muscle training tasks with visual targets presented for 3 s during physical exercises, while the control group participated in regular physical exercises. The intervention lasted 16 weeks, during which KVA, UDVA, and accommodative sensitivity of children were measured before and after the intervention using a kinetic visual acuity tester, a standard logarithmic visual acuity chart lightbox, and a lens flipper.ResultsPost-intervention, the experimental group showed significant improvements in KVA, UDVA, and accommodative sensitivity (p < 0.05). The control group did not show significant changes in KVA and UDVA (p > 0.05), but did exhibit a significant improvement in accommodative sensitivity (p < 0.05). Additionally, children in the experimental group demonstrated significantly higher levels of KVA, UDVA, and accommodative sensitivity compared to the control group after the intervention (p < 0.05). A moderate positive correlation was found between KVA and both UDVA and accommodative sensitivity. KVA partially mediated the effect of additional visual tasks during physical exercise on UDVA in children (left eye 95% CI: 0.011—0.180; right eye 95% CI: 0.023—0.167). Moreover, KVA partially mediated the effect of additional visual tasks during physical exercise on accommodative sensitivity (95% CI: 0.021—0.245).ConclusionIncorporating additional visual tasks into physical exercise effectively enhances KVA, UDVA, and accommodative sensitivity in children. There is a significant positive correlation between KVA and UDVA as well as between KVA and accommodative sensitivity. These visual tasks directly impact UDVA and accommodative sensitivity and indirectly influence them through the mediating effect of KVA.